Public awareness towards recycling activities in Bandar Hilir, Melaka / Nuratirah Farisya Mohammad - Mohammad, Nuratirah Farisya (2021)
Recycling is an effort to collect, process and reuse used materials. Thus, recycling will turn waste into valuable resources. It can also reduce the use of natural materials, generate financial resources, and provide social benefits. This descriptive study has been conducted to look at recycling practices among the public in Bandar Hilir, Melaka and was conducted on 5th May 2021. The aim of this study is to evaluate the community awareness and knowledge on recycling among the community in Bandar Hilir, Melaka. Meanwhile, the objective of this study is divided into three that include; i) to study on recycling facilities in town center, ii) to identify the community knowledge and awareness in town center and iii) to propose and recommend recycling facilities in town center. By using a quantitative method, the instrument used in this study is a questionnaire that contains four sections related to the background of the respondents and questions related to the research study. In addition, a simple random sampling method was used, and it was managed to get a total of 49 respondents from the residents, visitors, hawkers and consisting of the publics in Bandar Hilir. Descriptive statistics with frequency, percentage were analyzed using Statistical Packages for Social Sciences (SPSS). The results of the study found that most respondents gave a positive perception of recycling practices. This is because 80% of respondents were aware on the colors, functions of the recycle bins and have knowledge on the items that can or cannot be recycled. Meanwhile, the others 20% of respondents stated that unstrategic recycle bin locations and lack of facilities, knowledge and awareness caused why they do not recycle. This shows that, it needs to make some changes in the recycling scheme to improve awareness on the importance of recycling. In the end of this research, some recommendations were recommended that include providing the strategic location for recycle bin at Jalan Parameswara, providing a recycling buy-back program at Dataran Pahlawan parking lot, providing a smart recycle bin at every open space area in Bandar Hilir, improving on recycling facilities and services by local authority and an establishment of educational recycling policies.